PENDAMPINGAN KEGIATAN MERDEKA BELAJAR KAMPUS MERDEKA MANDIRI BIDANG RISET BAGI MAHASISWA HUBUNGAN INTERNASIONAL UNIVERSITAS TANJUNGPURA - Alunaza, Hardi (Jurnal Abdi Insani, 2025)
Students today face serious problems in the field of research. First, there is a lack of motivation and interest in scientific research. Second, there is limited access to adequate literature and references. Third, there are difficulties in writing and presenting the results of their work. Fourth, a lack of understanding of methodology. Fifth, a lack of available guidance time and competent supervisors. Without proper guidance, students find it difficult to formulate problems, design experiments, or analyze their findings. To address the above issues, the Faculty of Social and Political Sciences facilitates students in the Merdeka Belajar Kampus Merdeka program in the field of student research. This program aims to develop students' academic abilities in conducting scientific research. The program runs for three months from August to December 2024 and employs three methods: preparation and orientation, mentoring and research writing, and evaluation and reporting. After completing the program, students successfully wrote a book chapter titled “The Impact of the Jakarta-Bandung High-Speed Rail Project on Infrastructure Development and Sustainable Cities in Indonesia.” The supervising lecturer encouraged students to continue innovating and conducting research, as well as mastering writing techniques, teamwork, communication, and upholding academic integrity.